Verandering en verhoging van die risiko tydens die termyn van die verskeringskontrak - Stander, A.L.; Kloppers, H.J. (Juta, 2017)
The current rule in insurance law is that a duty to disclose material facts before the conclusion of the contract rests on both parties to the insurance contract. The test for materiality is based on the judgment of the reasonable person which is an objective measure. In terms of section 53 of the Short Term Insurance Act misrepresentation and non-disclosure by one of the parties is also judged objectively with reference to the view of the reasonable person. In the South African insurance law no common-law duty exists to extend the duty to disclose beyond the conclusion of the contract. However, nothing prevents the insurer from including such a clause in the contract. After a thorough explanation of this duty, the (presumptuous?) question is asked whether, in the context of marine insurance a statutory duty to disclose should not be placed on the insured in instance where the circumstances change to such an extent that the risk undergoes a material degree of increase in occurring during the term of the insurance contract. This issue is examined and the consequences are spelled out.